(untitled) (Journal of Nepal Geological Society, 2006)
The Tapovan- Vishnugad Hydroelectric Project is located in the Dhauliganga and Alaknanda valleys, where the Central Crystallines are composed mainly of medium- to high-grade metamorphics represented by augen gneisses, metabasics, fine grained quartz-mica gneisses, micaschists, quartzites, and coarse-grained garnet-biotite-kyanite gneisses. Towards the south, they are thrust over the Lesser Himalayan rocks of the Garhwal Group along the Main Central Thrust. The study aims at modelling the effects of geological structures for determining the potentially fractured or weak zones in underground excavations. For this purpose, Q and RMR values are obtained for each rock type. The in situ deformation modulus, cohesion, and friction angle are estimated to design support systems in unstable zones.